Effect of inoculation method on the quality and nutritional characteristics of low-alcohol kiwi wine. (15th February 2022) - Huang, Jintao; Wang, Yaqin; Ren, Yichen; Wang, Xingnan; Li, Hongcai; Liu, Zhande; Yue, Tianli; Gao, Zhenpeng
Abstract: In order to prepare the kiwi wine with high nutritional characteristics and low alcohol content, the physicochemical properties, organic acids, monomer phenols, water-soluble vitamins and aroma of kiwi wine fermented by Saccharomyces cerevisiae and Wickerhamomyces anomalus in different inoculation method were analyzed. The results showed that the alcohol content of the three kiwi wines ranged from 5.3 to 5.5% (v/v). The lactic acid content of COF (inoculated with a mix of S. cerevisiae and W. anomalus ) low-alcohol kiwi wine was 10.99 mg/mL. The quercetin and catechin contents of WSF (sequential inoculation with W. anomalus followed by S. cerevisiae ) low-alcohol kiwi wine were significantly lower than those in the other kiwi wines. The aroma in COF and WSF low-alcohol kiwi wines were predominately from W. anomalus, while those in SWF (sequential inoculation with S. cerevisiae followed by W. anomalus ) low-alcohol kiwi wine were predominately from S. cerevisiae . Highlights: Quinine and citric acid were the major organic acids in low-alcohol kiwi wine. The major phenols of kiwi wines were protocatechuic acid, catechin and quercetin. The aromas present in COF and WSF were predominately from W. anomalus. The WSF low-alcohol kiwi wine had the highest sensory score. The alcohol content of the three kiwi wines ranged from 5.3 to 5.5% (v/v).